A Novel ZRS Mutation in a Balochi Tribal Family with Triphalangeal Thumb, Pre-axial Polydactyly, Postaxial Polydactyly and Syndactyly - VanderMeer, Julia E (2012)
Limb malformations are one of the most common types of human congenital malformations. Mutations in the ZRS enhancer of Sonic Hedgehog are thought to be responsible for preaxial polydactyly in multiple independent families. Here, we describe a large Balochi tribal family from Southern Punjab, Pakistan, with a variable set of limb malformations and a novel ZRS mutation. The family has a limb phenotype characterized by triphalangeal thumb, preaxial polydactyly and postaxial polydactyly. There is also a high degree of phenotypic heterogeneity with less common clinical findings in the affected family members that include osseous syndactyly of forth-fifth fingers, clinodactyly, hypoplasia of mesoaxial fingers, and bifid halluces. The presentation in most of the affected patients was bilateral and symmetrical. A heterozygous C>A mutation at position 287 of the ZRS enhancer (chr7:156,584,283; hg19) was detected in all affected subjects and is absent from four unaffected family members, 42 unrelated samples and multiple databases of human variation. Combined, these results identify a novel ZRS287 C>A mutation which leads to a variable spectrum of limb phenotypes.